2017
DOI: 10.4103/0366-6999.208232
|View full text |Cite
|
Sign up to set email alerts
|

Menorrhagia and Uterine Volume Associated with Lower Urinary Tract Symptoms in Patients with Adenomyosis

Abstract: Background:Adenomyosis is a gynecological disorder with symptoms most presenting as dysmenorrhea and heavy menstrual bleeding. However, the presence of lower urinary tract symptoms (LUTS) among women with adenomyosis remains unclear. This study was designed to determine the prevalence of LUTS and factors related to the severity of these symptoms in this population.Methods:From July 2016 to November 2016, a total of 298 untreated symptomatic adenomyosis patients and 280 age-matched controls were enrolled. Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…As previously mentioned, severely increased uterine volume causes abdominal discomfort, with symptoms including flatulence, distended abdomen, and lower urinary tract symptoms with adenomyosis. [ 3 ] Furthermore, a larger uterus may lead to DVT. When surgical intervention is necessary, total laparoscopic hysterectomy (TLH) is the preferred surgical treatment, and it has been found that reducing the uterine volume can expand the indications for and reduce the difficulty of TLH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, severely increased uterine volume causes abdominal discomfort, with symptoms including flatulence, distended abdomen, and lower urinary tract symptoms with adenomyosis. [ 3 ] Furthermore, a larger uterus may lead to DVT. When surgical intervention is necessary, total laparoscopic hysterectomy (TLH) is the preferred surgical treatment, and it has been found that reducing the uterine volume can expand the indications for and reduce the difficulty of TLH.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a large uterine volume could be a potential risk factor for an increase in the occurrence of moderate-to-severe lower urinary tract symptoms with adenomyosis. [ 3 ] It was also reported that larger tumors were more often complicated by deep venous thrombosis (DVT) in patients with uterine fibroids. [ 4 ] In our experience, a large uterus due to adenomyosis may lead to DVT.…”
Section: Introductionmentioning
confidence: 99%
“…Another feature associated with adenomyosis, and indirectly, with disease volume, is uterine volume. Li et al showed that large uterine size was independently associated with bothersome lower urinary tract symptoms (LUTS) and HMB, but not dysmenorrhea or chronic pelvic pain (CPP) [50]. Another group showed that smaller uteri were associated with more CPP (8).…”
Section: Uterine Volumementioning
confidence: 99%
“…About a third of women with adenomyosis exhibit lower urinary tract symptoms, like pollakiuria, nocturia or dysuria, and those symptoms are positively correlated to an enlarged uterus and menorrhagia (43,44). Urinary incontinence (both urge and stress incontinence) are also associated with adenomyosis, with a prevalence of 26% amongst women with adenomyosis (44).…”
Section: Symptomsmentioning
confidence: 99%